A UTILIZATION of MONITORING CARD IRON SUPLEMENT IN THE EAST KELAYAN PRIMARY HEALTH CENTER - darmayanti, darmayanti; Rizani, Ahmad (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2023)
Anemia in pregnancy in Indonesia is 48.9% and 84.6% occurs in the age group of 15-24 years. Anemia in the first trimester (<12 weeks) will increase the risk of Small Gestational Age (SGA), namely the occurrence of abortion or premature birth. Another impact of anemia in pregnancy is on the mother (susceptible to infection, bleeding and even maternal death) whereas in babies with LBW, the baby's Hb level is low, inhibiting the baby's brain development. Supplement Iron pregnancy) as an important and effective effort in preventing and treament anemia due to iron deficiency by consuming at least 90 tablets during pregnancy. This community service activity in the working area of the Kelayan Timur Primary Health Center (PHC) in Banjarmasin involving elements from the leadership of the Health Service, PHC, 2 midwives, 2 nutritions and 21 health cadres. The implementation began in the PHC hall with opening activities, socialization, SGD facilitator training by 3 lecturers and 3 Polkessin Midwifery students. Furthermore, health cadres screened pregnant women with the approval of the midwife. SGD is carried out at Integrated PHC and PHC with the active participation of pregnant women and their companions as well as facilitators (team, midwives and health cadres) to understand iron supplementation and how to fill out iron consumption monitoring cards. Checking the initial Hb level and monitoring the filling of the monitoring card and compliance with iron supplement consumption every 30 days by students and health cadres. After 90 days, the final Hb level was evaluated. There was an increase in compliance with iron supplement consumption by 20% (1st month 68.9%; 3rd month 88.9%) and a 10% decrease in the incidence of anemia in pregnancy.